The Effectiveness of Implementing Academic Information System (SIAKAD) in Student Grades Management at the Sekolah Tinggi Agama Islam Terpadu - Herwinsyah (Al-fahim : Jurnal Manajemen Pendidikan Islam, 2024)
Student grade management is crucial for determining graduation, scholarships, and career paths. SIAKAD is expected to provide an effective solution by ensuring accuracy and transparency. However, its effectiveness needs further investigation as technological implementation often faces technical challenges and user acceptance at STAIT. This study aims to evaluate the effectiveness of the Academic Information System (SIAKAD) in managing student grades at STAIT Yogyakarta. The primary focus of this research is on how SIAKAD has been used by lecturers over the past semester to manage attendance, monitor lectures, and administer student grades. Through interviews with three lecturers who have experience teaching courses related to information technology, the study found that SIAKAD has provided significant ease in handling both administrative and academic tasks. These lecturers reported increased efficiency in recording attendance and managing grades, as well as benefiting from SIAKAD's ability to systematically monitor the progress of lectures. The system also supports more objective and accurate assessments, making it easier for lecturers to provide timely feedback to students. Although there were some challenges, such as adapting to new technology, overall, SIAKAD is considered a highly valuable tool in improving the quality of academic management at STAIT. The findings of this research indicate that the integration of information technology through the use of SIAKAD not only simplifies the work of lecturers but also enhances transparency and accountability in managing student grades. This conclusion highlights the importance of technological support in education, particularly in a higher education environment that is increasingly complex and demands high efficiency.